THE IMPORTANCE OF EDUCATION IN THE ADVENTURES OF TOM SAWYER - Niyazova Mokhichekhra Khayatovna; Qóshayeva Faridabonu Afzal qizi (Web of Journals Publishing, 2024)
This article analyzes the importance of education and learning in Mark Twain’s classic novel, The Adventures of Tom Sawyer. It reviews previous literary criticism and interpretations related to the theme of education in the novel. The analysis finds that education and learning serve both thematic and character development purposes in the story. Formal schooling is portrayed as tedious at times, but ultimately important for the characters’ moral and intellectual growth. Informal learning and experience also play a central role, as many of the most important lessons the characters learn take place outside of the classroom. The discussion examines how Twain used the theme of education to criticize certain aspects of society and human nature while also affirming a philosophy of hope in the power of knowledge and compassion to create positive change.
Keywords: The Adventures of Tom Sawyer, Mark Twain, education, learning, literature.